A&T Ethiopia Adolescent Nutrition Endline Survey 2021: Health Extension Worker - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Alive & Thrive (A&T) is an initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding, and complementary feeding practices. In Ethiopia, A&T implemented a package of adolescent nutrition interventions through school-based (nutrition messages during flag assemblies, classroom lessons on nutrition, student clubs on nutrition for girls, peer mentoring on nutrition, body mass index (BMI) measurement with counseling, and parents’ meetings) and community platforms (health post and home visits and community gatherings to discuss adolescent nutrition). This dataset is part of a survey that was conducted to gather endline data for the impact evaluation of the interventions. The overall study objective was to determine the feasibility of delivering nutrition interventions primarily through school-based platforms and their impact on diet quality among adolescent girls. Research questions include: 1) What is the program impact on the diet of adolescent girls: (1) dietary diversity, (2) meal frequency, and (3) less consumption of unhealthy snacks? 2) What is the exposure to adolescent nutrition interventions delivered through school-based platforms? 3) What factors influenced the integration of adolescent nutrition interventions into school-based platforms and their outcomes? The evaluation used a two-arm cluster-randomized, non-masked trial design, consisting of two cross-sectional surveys of in-school adolescent girls aged 10-14 years enrolled in grades 4-8. The unit of randomization is the primary school which includes grades 1-8. The endline survey was conducted in March-April 2021 by Addis Continental Institute of Public Health (ACIPH), the in-country research collaborator for the survey. The endline survey included the following: 1) Adolescent girl questionnaire, 2) Parent questionnaire, 3) Teacher/Principal questionnaire, 4) Primary school observation checklist, and 5) Health Extension Worker (HEW) questionnaire. The HEW interviews were conducted using pretested, structured questionnaires. Information was collected on HEW background, school and community role, nutrition-related activities, perceptions/beliefs, nutrition knowledge, effect of COVID-19 on workload or work activities, and receipt of COVID-19 training or guidelines.